The Challenging Task of Measuring Home Cooking Behavior. - Raber, Margaret (J Nutr Educ Behav, 2021)
The link between home cooking and health is being actively explored in both observational and experimental studies. However, research on this topic is limited by the lack of cooking behavior metrics. Most existing assessment tools focus only on cooking frequency or one’s ability to complete specific a priori food preparations. Cooking is a complex and multifaceted behavior that is influenced by culture, environment, and social norms. More flexible and adaptable measurement approaches are needed to elucidate the spectrum of cooking ability in the population and, in turn, develop meaningful recommendations and interventions.